Crucial Decisions Needed: English in Science and Teaching in Non-Anglophone Countries - de Wit, Hans; Unangst, Lisa; Altbach, Philip (International Higher Education, 2022)
English is the dominant language of instruction and scientific reporting worldwide. There is an increasing need to access scientific research in other languages and from other regional and cultural backgrounds. Non-Anglophone countries need to find a balance between quality of education, service to their own students, efforts to widen access, and national identity, as well making their higher education attractive to international students.